Broad-Spectrum Antibacterial Peptide Kills Extracellular and Intracellular Bacteria Without Affecting Epithelialization - Nepal, Anala; Ræder, Synnøve Brandt; Søgaard, Caroline Krogh; Haugan, Maria Schei; Otterlei, Marit (Frontiers in Microbiology, 2021)
New antibacterial drugs with novel modes of action are urgently needed as antibiotic resistance in bacteria is increasing and spreading throughout the world. In this study, we aimed to explore the possibility of using APIM-peptides targeting the bacterial β-clamp for treatments of skin infections. We selected a lead peptide, named betatide, from five APIM-peptide candidates based on their antibacterial and anti-mutagenic activities in both G+ and G- bacteria. Betatide was further tested in minimal inhibitory concentration (MIC) assays in ESKAPE pathogens, in in vitro infection models, and in a resistance development assay. We found that betatide is a broad-range antibacterial which obliterated extracellular bacterial growth of methicillin-resistant Staphylococcus epidermidis (MRSE) in cell co-cultures without affecting the epithelialization of HaCaT keratinocytes. Betatide also reduced the number of intracellular Staphylococcus aureus in infected HaCaT cells. Furthermore, long-time exposure of betatide at sub-MIC concentrations induced minimal or no increase in resistance development compared to ciprofloxacin, and gentamicin or ampicillin in S. aureus and Escherichia coli. These properties support the potential of betatide for the treatment of topical skin infections.